Changing the face of reference and user services: adoption of social media in top Ghanaian academic libraries. Issue 3 (8th August 2016) - Ahenkorah-Marfo, Michael; Akussah, Harry
Abstract : Purpose: Social media allows collaboration, participation and sharing in libraries with users. The purpose of this research is to examine the response of academic librarians in Ghana to the use of social media in reference and user services. Design/methodology/approach: It is a quantitative study that employed the Likert type of questionnaire in soliciting the views of academic librarians from six public and private universities in Ghana on their knowledge and use of social media in providing reference and user services. Findings: The findings of the study indicate that majority of academic librarians are knowledgeable and use social media for both personal and work-related purposes. They however, lack adequate skills to use the array of social media tools to make remarkable difference in service delivery. For this reason, they find the traditional mode of service delivery a comfort zone. Practical implications: Higher education policy makers in Ghana and elsewhere would find the results useful in decisions on the types of social media tools to use in universities and colleges. Originality/value: The study provides in-depth analysis of the impact of social media on reference and user services in Ghanaian libraries, which is deficient in literature. It also recommends change in policy direction and training to whip up interest in librarians to use social media.